Assessing the efficacy of monosodium glutamate as a growth enhancer in broiler chicken production - Osman, Ibrahim; Mohammed, Alhassan (Asia Pacific Network for Sustainable Agriculture, Food and Energy Network (SAFE Network), 2021)
The purpose of this research was to assess the efficiency of monosodium glutamate (MSG) as growth promoter in broiler chicken production. The study evaluated the effect of varying concentrations of MSG in the drinking water of broiler chickens on their growth performance, carcass characteristics and caecal Escherichia coli population. Ninety (90) chicks at 21 days of age were randomly selected and assigned to 5 treatment groups (0g/L, 2g/L, 3g/L, 4g/L and 5g/L) of MSG concentrations in a Completely Randomized Design (CRD) with 18 chicks per treatment and 6 chicks per replicate. MSG was administered in the drinking water. Feed and water were given ad-libitum and light provided 24 hours. The parameters measured were feed intake, weight gain, feed conversion efficiency, carcass dress weight, digestive organ traits and caecal Escherichia coli concentrations. Data collected were analysed using one-way ANOVA in GenStat (version 8). The results of the study showed an improvement (P<0.05) in feed intake and daily weight gain at 5g/L concentration and the highest (P<0.05) feed conversion efficiency was achieved at concentrations of 2 and 3g/L respectively. Carcass dress weight, liver and intestinal weights increased (P<0.05) at a concentration of 5g/L. However, those group of birds on 2g/L MSG concentration had the highest (P<0.05) heart weight and those of birds in the control had the highest (P<0.05) intestinal length. Escherichia coli concentration in the caeca reduced (P<0.05) as the concentration of MSG increased in the drinking water of birds. In conclusion, MSG supplementation in broiler chickens production could improve growth performance and reduce pathogenic microbes especially E. coli.